(untitled) (Journal of Sciences & Technology, 2019)
In the mechanical industry, the success and the results obtained by the heat treatments in the improvement of the properties of mechanical parts and mechanisms, with the introduction of new alloy and composite materials, found that the introduction of other techniques is issentiels, The metal parts subject to wear must be hard, but the hard metals can be brittle, fragile and difficult to work. A solution to this dilemma may consist in manufacturing the parts in a relatively soft and resistant alloy and then modifying its surface by the action of an appropriate treatment. The application of surface treatments by the various spray coating techniques allow a considerable contribution to be made in order to improve the properties of resistance to wear, the friction and to increase the life time in the mechanical parts.